Improving complex special physical preparedness rugby players 16–18 years - Volodymyr Ashanin; Vladlena Pasko; Oleg Podolyaka; Anatoliy Rovnyy; Valeriy Yermolaiev (Слобожанський науково-спортивний вісник, 2015)
Purpose: to work out the program of the special physical preparation of rugby-players of 16–18 years and to investigate the dynamics of indexes of the special physical preparedness with the use of computer technologies. Material and Methods: 60 sportsmen took part in age of 16–18 in research. Results: the complex program of the special physical preparation of sportsmen on the stage of the specialized preparation and results of experimental verification of its introduction is presented. Conclusions: during a pedagogical experiment efficiency of application of the worked out experimental program is well-proven for perfection of educational-training process of rugby-players of 16–18 years, that being confirmed by research results.